The Impact of Smart Tourism Technology on Tourist Satisfaction Moderating By Digital Literacy - Yusminar Wahyuningsih; Cahyani Pratisti (International Journal of Multidisciplinary Sciences and Arts, 2026)
The rapid advancement of smart tourism technology has significantly transformed tourist–destination interactions, particularly in urban heritage destinations seeking to enhance service quality and competitiveness. Despite growing adoption, empirical evidence explaining how smart tourism technology influences tourist satisfaction, considering individual capabilities, remains limited. This study aims to examine the effect of smart tourism technology on tourist satisfaction, with tourist experience as a mediating variable and digital literacy as a moderating variable. The research was conducted in Malioboro, Yogyakarta, one of Indonesia’s most iconic urban heritage destinations that has implemented various smart tourism initiatives, including digital information systems, cashless payment services, and smart mobility solutions. Using a quantitative research approach, data were collected from 250 domestic and international tourists through structured questionnaires. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to test the proposed relationships among variables. The findings reveal that smart tourism technology has a significant positive effect on tourist satisfaction. Tourist experience is found to partially mediate the relationship between smart tourism technology and tourist satisfaction, indicating that technology enhances satisfaction primarily through enriched experiential value. Furthermore, digital literacy significantly moderates the relationship between smart tourism technology and tourist experience, suggesting that tourists with higher digital competence gain greater experiential benefits from smart tourism services. These results confirm the expected relationships and highlight the importance of aligning technological innovation with user capabilities. Practically, the study provides valuable insights for destination managers and policymakers to strengthen smart tourism strategies by improving both technological infrastructure and digital literacy programs, thereby supporting sustainable destination competitiveness.